2022
DOI: 10.1038/s41598-022-15854-8
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a novel signature and prediction of the immune landscape in gastric cancer based on necroptosis-related genes

Abstract: Necroptosis, a type of programmed cell death, has become a potential therapeutic target for solid tumors. Nevertheless, the potential roles of necroptosis-related genes (NRGs) in gastric cancer (GC) remain unknown. The objective of the present study was to create a necroptosis-related prognostic signature that can provide more accurate assessment of prognosis in GC. Using The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) data, we identified differentially expressed NRGs. Univariate analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…In this context, they may contribute to a chronic in ammatory environment that supports tumor progression and fails to adequately modulate the tumor microenvironment. Our ndings align with and extend previous studies [4,22,23] . The study by Dai et al con rmed that the risk scores derived from six LMAGs through univariate and multivariate Cox regression analysis showed that the HRisk group had higher immune and stromal scores and lower tumor purity scores.…”
Section: Discussionsupporting
confidence: 93%
“…In this context, they may contribute to a chronic in ammatory environment that supports tumor progression and fails to adequately modulate the tumor microenvironment. Our ndings align with and extend previous studies [4,22,23] . The study by Dai et al con rmed that the risk scores derived from six LMAGs through univariate and multivariate Cox regression analysis showed that the HRisk group had higher immune and stromal scores and lower tumor purity scores.…”
Section: Discussionsupporting
confidence: 93%
“…Necroptosis has a prominent role in tumorigenesis, tumor progression, cancer metastasis and prognosis, and immune regulation [ 8 , 9 ]. Necroptosis may contribute to the augmented therapeutic efficiency of tumors by accelerating cancer cell death or enhancing the sensitivity of tumor cells [ 10 , 11 ]. Some studies have reported the necroptosis-related gene (NRG) signature can predict poor prognosis in some human cancers, including NSCLC [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The infiltration scores of 16 immune cells and the activities of 13 immune-related pathways were calculated using the GSVA software package employing the ssGSEA method 55 . Marker genes of various immune cells were obtained from previous studies 56 and are listed in Table S2 .…”
Section: Methodsmentioning
confidence: 99%